Methods (Procedures) of Audit of Commercial Bank Assets - Prykhodko, Roman (Metody (procedury) audytu aktywów banków komercyjnych, 2010)
Recently, Ukrainian economy has become more and more integrated into the international economy. This matter has also become of a great importance for the financial sector of Ukrainian economy. During the period of 2005-2010 several sound acquisitions in banking sector took place and still banks of Ukraine are very interesting for foreign investors. The issue of transparency becomes more and more important. The problem of correspondence between methods and procedures of audit of commercial bank assets used in Ukraine and worldwide is still urgent and timely. Till now internal auditors of Ukrainian commercial banks and small audit companies in Ukraine mainly use the documentary inspections of the main part of sample. At the same time International Standards of Audit highly encourages auditors to use other methods such as test of controls and analytical procedures.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 151-158
Keywords: methods; audit; bank; assets